Non‐technical skills in paramedicine: A scoping review. (8th September 2020) - Bennett, Ryan; Mehmed, Niall; Williams, Brett
Abstract: This scoping review aims to identify which non‐technical skills have been empirically identified in the literature, to create the first list of empirically identified non‐technical skills for paramedics and allied health personnel. A five‐stage scoping literature was undertaken in March 2020. The search retrieved a total of 4756 citations. A total of 93 studies met the inclusion criteria and were analyzed for data charting. A total of 26 non‐technical skills were identified in the literature. The top five non‐technical skills included decision‐making (33%, n = 31), communication (24%, n = 23), empathy (17%, n = 16), leadership (12%, n = 12), and ethics (10%, n = 10). Furthermore, only five studies investigated the assessment or measurement of non‐technical skills. This scoping review identified 26 non‐technical skills that had been investigated in the paramedic literature to create the first list of empirically based desirable non‐technical skills for a paramedic. Subsequently, research can then begin to focus on identifying the link that these have to paramedic practice and patient safety.